Conflict Escalation in Myanmar After Military Junta Coup - Yuliana Anggun Pertiwi (Journal of Law, Politic and Humanities, 2025)
This research aims to analyze the escalation of conflict in Myanmar after the military coup in 2021 with a research focus on understanding the dynamics of conflict during military junta rule and its impact on domestic and regional situations. This research uses a qualitative method with a descriptive-analytical approach, relying on secondary data sources, namely literature studies from various sources. The results show that the coup carried out by the military junta has overthrown the legitimate government. Instead of creating stability, this attitude triggered massive rejection by the people of Myanmar. This condition was responded aggressively by the junta, thus increasing tension and violence in various regions. ASEAN has attempted to mediate the conflict through the Five-Point Consensus, but it did not produce significant results because the military junta did not show commitment in implementing the agreement. Opposition groups such as the National Unity Government (NUG) and People's Defense Force (PDF) that were previously not major actors in the armed conflict are now increasingly active against the junta, joining forces with armed ethnic groups to overthrow the military government. This resistance has weakened the junta's control over Myanmar, indicating the potential for a greater transition of power in the future.